Male Infertility Increases the Risk of Cardiovascular Diseases: A Nationwide Population-Based Cohort Study in Taiwan - Peng-Ciao Chen; Yu-Ju Chen; Chia-Chen Yang; Ting-Ti Lin; Chien-Chu Huang; Chi-Hsiang Chung; Chien-An Sun; Wu-Chien Chien (The World Journal of Men's Health, 2022)
Purpose:Purpose: Some evidence suggests that male infertility increases the risk of cardiovascular diseases (CVDs). However, the evi-dence in Asian populations is relatively scarce. The aim of this study is to determine whether male infertility increases the risk of CVDs. Materials and Methods:Materials and Methods: We used inpatient and outpatient data for the years 2000 to 2015 from the Taiwanese Longitudinal Health Insurance Database. We enrolled 7,016 males over 18 years old and diagnosed with male infertility. Of these, 2,326 matched our inclusion criteria and were assigned to the study group. For each infertility patient, four comparison patients were frequency-matched by age and index date to form a control cohort comprising 9,304 patients. Cox proportional haz-ards analysis was used to estimate the association between male infertility and CVDs. Results:Results: After a 15-year follow-up, the incidence rate of CVDs was higher in the infertility group than the control group (1,460.23 and 1,073.70 per 100,000 person-years, respectively). The Cox proportional hazards regression analysis revealed that the adjusted HR for CVDs was 1.472 for the infertility group (95% CI, 1.288–1.683; p<0.001) relative to the control group. The Kaplan–Meier analysis of the cumulative incidence of CVDs in the two groups showed that the cumulative risk curve for CVDs was significantly higher for the infertility group than the control group. Conclusions:Conclusions: This study shows that men with infertility have a higher risk of developing incident CVDs. In the future, health-care providers should pay attention to these patients because of their higher health risks.